2013
DOI: 10.1002/oby.20354
|View full text |Cite
|
Sign up to set email alerts
|

CD36 is important for adipocyte recruitment and affects lipolysis

Abstract: Objective: The scavenger receptor CD36 facilitates the cellular uptake of long-chain fatty acids. As CD36-deficiency attenuates the development of high fat diet (HFD)-induced obesity, the role of CD36-deficiency in preadipocyte recruitment and adipocyte function was set out to characterize. Design and Methods: Fat cell size and number were determined in gonadal, visceral, and subcutaneous adipose tissue of CD36 À/À and WT mice after 6 weeks on HFD. Basal lipolysis and insulin-inhibited lipolysis were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
7
43
0
Order By: Relevance
“…Isolated adipocytes from CD36 KO mice have impaired NEFA uptake (Coburn et al, 2000). Furthermore, CD36-deficient mice do not develop diet-induced obesity, suggesting that adipocyte hypertrophy is impaired in these mice (Hajri et al, 2007;Koonen et al, 2010;Vroegrijk et al, 2013). We speculate that increased circulating lipid causes adipocyte hypertrophy and adipose growth, but there is currently limited evidence to show clearly that circulating lipid levels induce a hypertrophic morphology, as defined by Arner et al (2010).…”
Section: Availability Of Lipid As a Rate-limiting Step For Adipocyte mentioning
confidence: 79%
“…Isolated adipocytes from CD36 KO mice have impaired NEFA uptake (Coburn et al, 2000). Furthermore, CD36-deficient mice do not develop diet-induced obesity, suggesting that adipocyte hypertrophy is impaired in these mice (Hajri et al, 2007;Koonen et al, 2010;Vroegrijk et al, 2013). We speculate that increased circulating lipid causes adipocyte hypertrophy and adipose growth, but there is currently limited evidence to show clearly that circulating lipid levels induce a hypertrophic morphology, as defined by Arner et al (2010).…”
Section: Availability Of Lipid As a Rate-limiting Step For Adipocyte mentioning
confidence: 79%
“…(79) A study of CD36 knockout mice revealed reduced bone quantity, suggesting that CD36 is important for skeletal health. (79) A study of CD36 knockout mice revealed reduced bone quantity, suggesting that CD36 is important for skeletal health.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were processed for adipocyte size determination as previously described [18]. Adipocyte number per fat pad was calculated from the fat pad mass and adipocyte size.…”
Section: Methodsmentioning
confidence: 99%